Geotechnical Mapping for Soil Physical and Mechanical Parameters and Hard Soil Depth in Badung Regency - Zefira Wisna Maulidha; Trihanyndio Rendy Satrya; Yudhi Lastiasih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
The infrastructure is important for the great life of a region and most of the country. Therefore, infrastructure must be always in proper condition in its functionality. Furthermore, it must follow the main principle which is infrastructure asset management. In this case, geotechnical mapping is also related to the principles of Infrastructure Asset Management in planning, designing, and feasibility studies of an infrastructure project in Badung Regency, hence the infrastructure projects are better prepared. The research methods include collecting soil investigation data, processing soil investigation data, describing the results of soil investigation data with mapping tools, and geotechnical zoning with statistical analysis. The results obtain geotechnical map of Badung Regency in 2 and 3-dimensional form. The 2D results in the form of a hard soil depth map can be concluded that South Kuta District has a variation depth of 0.4 – 15 meters, North Kuta District has a variation depth of 1.5 – 5 meters, Kuta District has a variation depth of 1.5 – 10 meters, Mengwi District has a variation depth of 1.5 – 10 meters, Abiansemal District has a variation depth of 5-15 meters, Petang District has a variation depth of 5-22 meters. The 3D Zone 1 lithology map can be concluded that Zone 1 area covered with hard soil depth around 5 – 10 meter is dominated by sandy silt, silty sand, sand and a little clayey silt. That area covered with hard soil depth about 1.5 – 5 meter is dominated by clay, clayey silt, sandy silt, silty sand and sand with heterogeneous distribution. The Zone 1 area is dominated by the specific volume saturated value (γsat) range of 1.5 – 2.0 t/m3. The values > 2.0 t / m3 is found in Sading area with hard soil depth of 5-10 meters. The Zone 1 area is dominated by the range of N-SPT values = 0 - 30. The N-SPT values > 30 are found in Sading area with hard soil depth 5-10 meters.